Governance, Ethics, and Policymaking: The Role of Interdisciplinary Research in Addressing Contemporary Political Challenges - Prachamon, Taksin (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper examines the role of interdisciplinary research in addressing contemporary political challenges, with a focus on governance, ethics, and policymaking. As global issues such as climate change, digital transformation, and social justice continue to evolve, traditional governance models often struggle to provide effective solutions. The study explores how integrating diverse academic perspectives - ranging from political science and economics to environmental studies and ethics - can enhance policy formulation and implementation. Special attention is given to the ethical dimensions of policymaking, including transparency, accountability, and public participation, which are crucial in fostering democratic governance. The research highlights case studies where interdisciplinary approaches have successfully influenced policy outcomes, demonstrating their value in tackling complex societal issues. By emphasizing the necessity of collaborative frameworks that bridge the gap between scientific research and policy execution, this paper advocates for a governance model that is adaptive, evidence-based, and ethically grounded. The findings contribute to the ongoing discourse on strengthening governance structures through holistic, multidisciplinary strategies.